2013
DOI: 10.4236/ojo.2013.37055
|View full text |Cite
|
Sign up to set email alerts
|

Phantom Fighters: Coping Mechanisms of Amputee Patients with Phantom Limb Pain: A Longitudinal Study

Abstract: Phantom Limb Pain (PLP) is a phenomenon commonly observed in orthopedic rehabilitation units that can have detrimental effects on patients' functioning. Psychological aspects of PLP have been widely investigated showing that some coping mechanisms are advantageous at certain points but not at others. However, the mechanisms related to positive adjustment to PLP during the course of rehabilitation have not been adequately examined. The aim of the study was to investigate the relationship between PLP and coping … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 44 publications
(48 reference statements)
0
2
0
1
Order By: Relevance
“…Pain from the phantom limb may also exacerbate feelings of depression ( Murray and Forshaw, 2013 ), cause mood dysregulation ( Trevelyan et al, 2016 ) and predispose the person to accidents ( Senra et al, 2012 ). Generally, these false sensations are reported in 50–85% of amputees, with varying intensity and duration, spanning weeks or months after surgery ( Margalit et al, 2013 ). This aspect of amputation generates frustration and stress and it can become a threat to the rehabilitation process and the psychological and physical well-being of the person.…”
Section: Discussionmentioning
confidence: 99%
“…Pain from the phantom limb may also exacerbate feelings of depression ( Murray and Forshaw, 2013 ), cause mood dysregulation ( Trevelyan et al, 2016 ) and predispose the person to accidents ( Senra et al, 2012 ). Generally, these false sensations are reported in 50–85% of amputees, with varying intensity and duration, spanning weeks or months after surgery ( Margalit et al, 2013 ). This aspect of amputation generates frustration and stress and it can become a threat to the rehabilitation process and the psychological and physical well-being of the person.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have reported factors that may be related to the risk of developing chronic pain following an amputation – time elapsed since amputation, 18 presence of pain before amputation, 19 higher levels of pain soon after amputation, 20 psychologic factors, 21 intensity of concomitant nonpainful phantom limb sensations, 22 and the site of amputation. 23 Objective methods have demonstrated changes in both the peripheral and central nervous systems, including neuroimaging and neurophysiologic techniques, in patients with chronic phantom pain after an amputation.…”
Section: Introductionmentioning
confidence: 99%
“…Szilárdabb abbéli hitük, hogy nem képesek maguk irányítani sorsukat, így önmagukkal szemben jóval kritikusabbak, kevésbé érzik értékesnek magukat. Amputáció következtében a személy megcsonkítottnak, üres-nek, sérülékenynek érzi magát, sok esetben nehezen tud megküzdeni új korlátaival (Margalit, Heled, Berger, & Katzir, 2013). A tükörben végzett gyakorlatok mindezek ellenére javulást eredményeztek az önértékelésben is, de az egészséges önbizalom helyreállítása több idõt igényel.…”
Section: Megbeszélésunclassified